2013
DOI: 10.1248/cpb.c12-01100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carotenoid Fatty Acid Esters from the Peels of the Persimmon <i>Diospyros kaki</i>

Abstract: Separation and structural determination of the chloroform-soluble components obtained from the peels of the persimmon (Diospyros kaki Thunb.) were performed. β-Carotene, lycopene, β-cryptoxanthin monomyristic acid ester, zeaxanthin di-myristic acid ester, the latter two of which were accompanied by a small amount of palmitoleic acid in the fatty acid moiety, and oleanolic acid were identified. Among these components, the mono-fatty acid ester of β-cryptoxanthin and the di-fatty acid ester of zeaxanthin were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Mercadante et al (2017) [37] reported that reliable identification of carotenoid esters based only in the elution order or retention time is not possible and can lead wrong assignments due to co-elution or poor baseline separation. In the present study, no problems were found to assign hydrocarbon carotenoids as showed Previous studies about the carotenoid and carotenoid esters composition of persimmon peel [15] reported the presence of β-carotene, lycopene, β-cryptoxanthin mono-myristic acid ester, zeaxanthin di-myristic acid ester, using silica gel chromatography followed by structural characterization by 1 H-NRM and 13 C-NMR.…”
Section: Xanthophyll Esterssupporting
confidence: 49%
See 1 more Smart Citation
“…Mercadante et al (2017) [37] reported that reliable identification of carotenoid esters based only in the elution order or retention time is not possible and can lead wrong assignments due to co-elution or poor baseline separation. In the present study, no problems were found to assign hydrocarbon carotenoids as showed Previous studies about the carotenoid and carotenoid esters composition of persimmon peel [15] reported the presence of β-carotene, lycopene, β-cryptoxanthin mono-myristic acid ester, zeaxanthin di-myristic acid ester, using silica gel chromatography followed by structural characterization by 1 H-NRM and 13 C-NMR.…”
Section: Xanthophyll Esterssupporting
confidence: 49%
“…Persimmon carotenoid profile had been reported by several authors [13,14,9], but in all of these studies only saponified extracts were characterized and in all cases a C18 column was used by HPLC carotenoid separation, being trans-β-cryptoxanthin, trans-zeaxanthin, trans-lutein, trans-βand α-carotene and lycopene the major carotenoids found in these saponified extracts. Only, Hitaka et al (2013) [15] reported the characterization of carotenoid fatty acid esters from persimmon peels using the isolation of the main carotenoids and their esters by purification via silica gel column chromatography and the characterization of their structures buy using HR-FAB-MS, 1 H-and 13 C-NMR. β-carotene, lycopene, β-cryptoxanthin mono myristic acid ester, zeaxanthin di-myristic acid ester, and small amounts of xanthophyll esters of palmitoleic and oleanolic acid were found.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the mode at 2929 cm −1 represents C‐H stretching and arises from methyl units . Ester carbonyl groups (C=O), mainly sourced from acetyl group of glucomannan and hemicellulose appear at 1732 cm −1 while the C=O stretch vibration from GM with the contribution of protein amide groups may be found at 1635 cm −1 . In addition, the C‐O‐C fragment was observed at 1154 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Esters of carotenoid fatty acids ( Diospyros kaki THUNB. ), lycopene, β-carotene, ester of zeaxanthin di-myristic acid, and mono-myristic acid ester of β-cryptoxanthin have all been characterized in the persimmon peel, while a small quantity of palmitoleic acid in the fatty acid and oleanolic acid fraction was found [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In persimmon extracts, organic acids (malic, oxoglutamic, citric, succinic, and aspartic), amino acids (gamma-aminobutyric acid (GABA), alanine, arginine, valine, leucine, and isoleucine), fatty acids (palmitoleic acid methyl ester, myristic acid, and linoleic acid) [ 40 , 52 ], vitamins (trigonelline and ascorbic acid), α-tocopherol, oleanolic acid, betulinic acid, β-sitosterol, and uridine have also been identified [ 40 ].…”
Section: Introductionmentioning
confidence: 99%